DARE Newsletter, Vol. 14, No. 1, Winter 2011 - DARE; Hall, Joan Houston; Risteen, Landon (Dictionary of American Regional English, 2011)
Contents: "From the Chief Editor's Desk" by Joan Houston Hall; "DARE Was There: The 1940s" by Landon Risteen; "Contributors to DARE in 2010"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States